Young Latinos Use of Mobile Phones: A Cross-Cultural Study - Albarran, Alan B. (2022)
This study is based on a large-scale project examining mobile phone use among young Latinos in six different countries: Argentina, Chile, Colombia, Mexico, the United States, and Uruguay. Following the uses and gratifications tradition as a theoretical framework, researchers used a two-stage research design involving both qualitative and quantitative research methodologies to analyze how young adult Latinos use their mobile phones, and the perceived gratifications obtained from their use and comparisons to other forms of technology. A total of 1,320 subjects were surveyed across the six countries, yielding a rich data set that is only partially examined in this particular paper. The results indicate similarities and differences among the six counties and offers both theoretical and practical findings, as well as suggestions for future research and investigation.